1963
DOI: 10.1126/science.139.3560.1212
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Corticosteroids: Changes in Concentration after Stimulation of Hippocampus and Amygdala

Abstract: Plasma 17-OH corticosteroid levels were determined before stimulation and at various intervals after stimulation in these limbic sites in patients in whom implanted electrodes had been placed during evaluation for surgical treatment of psychomotor epilepsy. Stimulation of the amygdala was followed by an elevation of plasma 17-hydroxycorticosteroids. Hippocampal stimulation resulted in a decreased corticosteroid level, followed in two instances by a secondary elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1964
1964
1992
1992

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(32 citation statements)
references
References 2 publications
2
30
0
Order By: Relevance
“…For example, destruction of the hippocampus or its efferents leads to increases in corticotropin and corticosterone under basal conditions (4-7) and during stress (5,6,8,9). Furthermore, stimulation of most parts of the hippocampus limits the extent of HPA activation to an array of stressors (10)(11)(12)(13). Our (15) and cannot account for the elevated post-stress titers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, destruction of the hippocampus or its efferents leads to increases in corticotropin and corticosterone under basal conditions (4-7) and during stress (5,6,8,9). Furthermore, stimulation of most parts of the hippocampus limits the extent of HPA activation to an array of stressors (10)(11)(12)(13). Our (15) and cannot account for the elevated post-stress titers.…”
Section: Resultsmentioning
confidence: 99%
“…Destruction of the hippocampus, for example, leads to hypersecretion of glucocorticoids under basal and stressed conditions (4)(5)(6)(7)(8)(9). Furthermore, stimulation of most parts of the structure inhibits stress-induced HPA activation (10)(11)(12)(13). At least some of this inhibitory influence of the hippocampus represents mediation of feedback inhibition by glucocorticoids.…”
mentioning
confidence: 99%
“…Approximately 50% of individuals with Alzheimer's disease (in which there is typically extensive damage to or isolation of the hippocampal formation) hypersecrete GCs (APA Taskforce, 1987), and those with severe damage to the hippocampal formation (as assessed by CT scan) are more hypersecretory than those with less hippocampal damage (De Leon et al, 1988). More direct evidence of the relationship between the human hippocampus and GC hypersecretion comes from an early study, carried out during neurosurgery, which reported that stimulation of the hippocampus inhibited adrenocortical secretion (Mandell et al, 1963). Nevertheless, there has been little sys- , 1989a).…”
Section: Inhibitionmentioning
confidence: 98%
“…28 Hippocampal activity normally inhibits the cortisol axis, as demonstrated by electrical stimulation in humans. 29 Damage to hippocampal neurons can therefore be followed by hypercortisolism. This may be due to either a lesioninduced loss of a feedback site in the hippocampal system or an enhanced stimulation causing basal hypersecretion.…”
Section: Discussionmentioning
confidence: 99%